DAMPAK INDEPENDENSI, KOMPETENSI, DAN PROFESIONALISME AUDIT INTERNAL TERHADAP KUALITAS AUDIT - Rahmawati, Renita; Mulyanti, Dwinta; Dewi, Nisa Amalia (Universitas Logistik dan Bisnis Internasional, 2025)
This research was carried out with the goal of examining the connection between the independence, competence, and professionalism of internal audits and the quality of auditing at PT. Maharlika Lintas Wahana, as well as to assess the impact of internal audit quality stemming from these three factors. To evaluate the research hypothesis that indicates a quality correlation among latent variables, a variance structure-based structural equation modeling (SEM) method known as least square path modeling (PLS-PM) was utilized. Data was gathered through a questionnaire. The data collection approach for this research involved conducting surveys and collecting necessary information through multiple methods, including fieldwork and library research. A total of 133 respondents were included in this research. The results of the research show that the calculated F-value of 30.005 is greater than the F-table of 2.67, which means that independence, competence, and professionalism at PT. Citra Maharlika Lintas Wahana have an effect on the quality of internal audits.